36 C/5 technical note and annexes 2012 -2013 (UNESCO ParisFR, 2011)
Presents the UNESCO Draft Programme and Budget 2012-2013 (known as Draft 36 C/5) to the Executive Board for consideration.
Keywords: UNESCO